Synthesis and characterization of 1,3-bis(4-bromophenyl)-5-propyl-1,3,5-triazinane - Lefrada, Leila; Bouchemma, Ahcene; Bouhenguel, Mustapha; Ferhati, Amel; Chebbah, Mahmoud (European Journal of Chemistry, 2012)
Condensation of n-propyl amine and 4-bromoaniline with formaline in basic solution gives 1,3-bis(4-bromophenyl)-5-(propyl)-1,3,5-triazinane. Structure of the synthesized compound was characterized by FT-IR and 1H- and 13C-NMR spectroscopy.